2004
DOI: 10.1111/j.1365-313x.2004.02270.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel reporter for intrachromosomal homoeologous recombination in Arabidopsis thaliana

Abstract: A reporter system using engineered introns as recombination substrates in the uidA (GUS) gene has been developed and characterized in Arabidopsis thaliana. The non-coding nature of the recombination substrate has allowed us to monitor recombination events between duplicated copies of the intron that are either identical (homologous recombination) or harbour sequence polymorphisms (homoeologous recombination). The effects of substrate length and divergence on the frequency of recombination events were examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 23 publications
2
64
1
Order By: Relevance
“…To study the effect of parental reproductive age on somatic mutation rates in the progeny, we made use of various Arabidopsis transgenic lines carrying mutated or fragmented versions of the uidA reporter gene encoding GUS (Liu and Crawford, 1998;Kovalchuk et al, 2000;Li et al, 2004;Azaiez et al, 2006;Van der Auwera et al, 2008). These mutation reporter lines carrying a nonfunctional uidA gene enabled us to score somatic frameshift mutations, base substitutions, intrachromosomal recombination (ICR), and transpositions events, which led to the formation of a functional uidA gene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To study the effect of parental reproductive age on somatic mutation rates in the progeny, we made use of various Arabidopsis transgenic lines carrying mutated or fragmented versions of the uidA reporter gene encoding GUS (Liu and Crawford, 1998;Kovalchuk et al, 2000;Li et al, 2004;Azaiez et al, 2006;Van der Auwera et al, 2008). These mutation reporter lines carrying a nonfunctional uidA gene enabled us to score somatic frameshift mutations, base substitutions, intrachromosomal recombination (ICR), and transpositions events, which led to the formation of a functional uidA gene.…”
Section: Resultsmentioning
confidence: 99%
“…7). It was shown that ICR rates increase with the length of the recombination intron substrate present in the uidA gene (Li et al, 2004). ICR rates are lower in transgenic line R2L1 carrying a 418-bp intron compared with line R3L30 having a 589-bp intron.…”
Section: Saal 2000)mentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether small heterologies within homologous sequences might influence the efficiency of recombination (homoeologous recombination), GUSbased recombination substrates that contained defined numbers of mismatches within the overlap were set up. The presence of mismatches indeed reduced recombination frequencies (Li et al, 2004;Opperman et al, 2004). It became clear that the sister chromatids play an important role in SHR; therefore, a system was established that permitted the analysis of interchromatid recombination .…”
Section: Multiple Variations Of the Shr Setupmentioning
confidence: 99%